2020
DOI: 10.1371/journal.pone.0230410
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in sensitivity of radiochromic 3D dosimeter based on rigid polyurethane resin by incorporating tartrazine

Abstract: We investigated the influence of incorporating tartrazine on the dose response characteristics of radiochromic 3D dosimeters based on polyurethane resin. We use three types of polyurethane resins with different Shore hardness values: 30 A, 50 A, and 80 D. PRESAGE dosimeters are fabricated with different chemical components and concentrations. Tartrazine (Yellow No. 5) helps incorporate a yellow dye to fabricate the dosimeter. Elemental composition is analyzed with the Z eff. Three sets of six different PRESAGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Among them, part A and part B correspond to aliphatic diisocyanates and polymers with hydroxyl functional groups, respectively. 58 The urethane group (−NCO) in the hard chain reacts with the hydroxyl group (−OH) in the polyol to form a carbamic acid group (−NHCOO−), as shown in the reaction scheme in Figure 1b. The PUI sample with a thickness of 1 mm was cut into long strips to facilitate the analysis of its self-healing behavior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, part A and part B correspond to aliphatic diisocyanates and polymers with hydroxyl functional groups, respectively. 58 The urethane group (−NCO) in the hard chain reacts with the hydroxyl group (−OH) in the polyol to form a carbamic acid group (−NHCOO−), as shown in the reaction scheme in Figure 1b. The PUI sample with a thickness of 1 mm was cut into long strips to facilitate the analysis of its self-healing behavior.…”
Section: Resultsmentioning
confidence: 99%
“…The self-healing PU–IPDI film, denoted as PUI, contains an IPDI monomer, part A and part B. Among them, part A and part B correspond to aliphatic diisocyanates and polymers with hydroxyl functional groups, respectively . The urethane group (−NCO) in the hard chain reacts with the hydroxyl group (−OH) in the polyol to form a carbamic acid group (−NHCOO−), as shown in the reaction scheme in Figure b.…”
Section: Resultsmentioning
confidence: 99%
“…The RPD has a density of 1.053 g/cm 3 , an effective atomic number of 11.1, and a dose sensitivity of 0.1010 Gy, whereas the PRE-SAGE® dosimeter has a density of 1.048 g/cm 3 , an effective atomic number of 7.45, and a dose sensitivity of 0.0089 Gy 1 . 35,41 The manufacturing process consisted of the following: (1) Part B was completely mixed with reporter chemical, radical initiator, solvents, and yellow dye; (2) Part A was then put into Part B, which was vigorously mixed;…”
Section: Solid Polyurethane-based Dosimeter Fabricationmentioning
confidence: 99%
“…A recent study demonstrated that PRESAGE with low Shore hardness presents lower sensitivity than PRESAGE with high Shore hardness. The study shows that the sensitivity of PRESAGE with high Shore hardness further increased by 36.6% upon incorporation with tartrazine [ 98 ]. However, PRESAGE exhibits a high effective atomic number, which compromised its water equivalency.…”
Section: Sensitivity and Linearity Of Presagementioning
confidence: 99%
“…Thus, the chemical reaction occurred at a longer period in the PRESAGE, which yielded a high Polymers 2022, 14, 2887 14 of 27 dose response. A recent study demonstrated that the incorporation of tartrazine did not influence the dose-rate dependency of PRESAGE [98]. The silicone-based radiochromic dosimeter has been developed and shows insignificant dose-rate dependency [110].…”
Section: The Dose Rate Dependencymentioning
confidence: 99%